[Professor Quintard Taylor speaking at MultiCultural Center dedication] (1982)
Professor Quintard Taylor speaking at the University Union plaza, where he presented a historical synopsis of Martin Luther King Jr.'s life (according to the January 19, 1982 issue of the Mustang Daily).Pictured behind Professor Taylor are President Baker and others, gathered in the University Union plaza area for the dedication.